Longer Internode with Same Cell Length: LcSOC1-b2 Gene Involved in Height to First Pod but Not Flowering in Lentil (Lens culinaris Medik.) - Kuzbakova, Marzhan; Khassanova, Gulmira; Jatayev, Satyvaldy; Daniyeva, Nurgul; Sweetman, Crystal; Jenkins, Colin L. D.; Soole, Kathleen L.; Shavrukov, Yuri (Plants (Basel), 2025)
Stem internode length determines height to first pod (HFP), an important trait for mechanical harvesting in legume crops. In the present study, this trait in lentil was (Lens culinaris Medik.) examined using scanning electron microscopy (SEM) of epidermal cells in stem internodes of two parents, Flip92-36L and ILL-1552, with long and short HFP, respectively. No significant differences in cell length, but differences in cell width were seen. This indicates that HFP was determined by cell number rather than cell length. The candidate gene family for HFP, Suppressor of Overexpression of Constans 1 (SOC1), a member of the MADS-box transcription factor family, controls both flowering time (FT) and HFP traits. Six LcSOC1 genes were identified in this study, and their expression was analysed. Most of the genes studied showed constitutive expression during vegetative growth, flowering, and seed development stages. Expression of LcSOC1-a seems to be involved in the transition to flowering and FT, whereas expression of LcSOC1-b2 was strongly associated with HFP but not FT. Two haplotypes with two SNP each were identified in LcSOC1-b2 among eight sequenced lentil accessions, and an SNP-based ASQ marker was developed and used for genotyping of a lentil germplasm collection. Significant association between LcSOC1-b2 haplotypes and HFP was found in this study, indicating a primary role for this gene in internode length, potentially by regulating cell number.